Proximity tourism and cultural amenities: Evidence from a regional museum card. Issue 1 (February 2021) - Bertacchini, Enrico; Nuccio, Massimiliano; Durio, Alessandra
Although cultural tourism has generated extensive literature, it has often overlooked proximity tourism practices and the determinants of visits to near-home cultural amenities, often located in rural destinations with lower market appeal. This article investigates visiting behaviors and characteristics of intra-regional flows from urban settings toward museums and heritage sites located in surrounding areas. We use a unique transactional data set of about 76, 000 subscribers to a regional museum card in Piedmont (Italy) to analyze visiting patterns in the 2011–2014 period from the city of Turin to out-of-town cultural institutions. Our empirical analysis shows that being male, having lower socioeconomic status, visiting home-based museums, and loyalty to the card program are the most relevant factors explaining propensity to out-of-town visits. At the same time, a clear polarization of visits between a limited number of cultural attractors and the tail of minor heritage sites suggests that differences in museum characteristics can generate distinct motivations for visits to the two types of cultural institutions. From a policy perspective, although a definitive evaluation of the effect of the museum card on proximity tourism cannot be undertaken, findings suggest that bundle of minor attractions and major urban museums can generate indirect network advantages, foster cultivation of taste, and eventually stimulate both the demand for regional destinations and the development of original cultural programs.